2016
DOI: 10.1212/wnl.0000000000002459
|View full text |Cite|
|
Sign up to set email alerts
|

Prespecified dose-response analysis for A Very Early Rehabilitation Trial (AVERT)

Abstract: Objective:Our prespecified dose-response analyses of A Very Early Rehabilitation Trial (AVERT) aim to provide practical guidance for clinicians on the timing, frequency, and amount of mobilization following acute stroke.Methods:Eligible patients were aged ≥18 years, had confirmed first (or recurrent) stroke, and were admitted to a stroke unit within 24 hours of stroke onset. Patients were randomized to receive very early and frequent mobilization, commencing within 24 hours, or usual care. We used regression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
117
1
13

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 184 publications
(140 citation statements)
references
References 22 publications
(30 reference statements)
1
117
1
13
Order By: Relevance
“…Especially close observation of neurological status and vital parameters (e.g., temperature together with fast escalating infection strategies) may reduce incidence of delirium as response to cerebral reaction to infection induced neurotoxic transmitters (Riedel et al, 2014). Furthermore, on the SU in our study delirium screening and evidence-based delirium management is part of daily routine, including nonpharmacological interventions and early mobilization (Bernhardt et al, 2016). Other studies in the field did not reported delirium-related structures and processes; hence a comparison is not feasible.…”
Section: Discussionmentioning
confidence: 82%
“…Especially close observation of neurological status and vital parameters (e.g., temperature together with fast escalating infection strategies) may reduce incidence of delirium as response to cerebral reaction to infection induced neurotoxic transmitters (Riedel et al, 2014). Furthermore, on the SU in our study delirium screening and evidence-based delirium management is part of daily routine, including nonpharmacological interventions and early mobilization (Bernhardt et al, 2016). Other studies in the field did not reported delirium-related structures and processes; hence a comparison is not feasible.…”
Section: Discussionmentioning
confidence: 82%
“…Adapted with permission from . 33 Finally, we repeated the regression analysis for the UC group alone because of the potential risk of any unmeasured confounding by treatment group (additional unmeasured differences between treatment groups). This repeat analysis (Table 14) indicated that the same factors were important within the UC group alone.…”
Section: Statistical Trial Resultsmentioning
confidence: 99%
“…Much of this work has already been published by the AVERT group. [30][31][32][33][34][35][36] We will also refer to two related studies that were nested within the AVERT programme. These studies contribute to the understanding of AVERT, but were not specifically included in the original Health Technology Assessment (HTA) programme trial application.…”
Section: Avert Programmementioning
confidence: 99%
See 1 more Smart Citation
“…Too often, our choice of intervention type, dose, or scheduling is arbitrarily assigned (as reflected in many meta-analyses of stroke rehabilitation interventions), with a ''more is better'' mantra that is likely too simplistic and may even be harmful at certain points in the recovery pathway. 39 In complex behaviour change research, we see increased attention on codesign of interventions with the health consumer 40 ; turning these types of interventions into standardized protocols for delivery in trials is not simple.…”
Section: Theme 3: Intervention Development Monitoring and Reportingmentioning
confidence: 99%